Rozwiąż równania:
e) 2x-(3x-7)/4=x+1
g) (x-1)/3-(x-2)/2=(2x-5)/6
i) (x+6)/2-(5+x)/3=(2-x)/6
j) (2x-3)/6-(8-x)/9=(x+13)/18
k) (x+3)/3- (2+x)/4= (3-2x)/12
l) 2x-(1-4x)=2+(8x-5)
ł) 7-(3x+4)=(x+1)-(2x+4)
m) 4-2(5-x) = x-4(x-1)

Tych wykreślonych w załączniku podpunktów proszę nie robić.

1

Odpowiedzi

2010-04-11T23:45:20+02:00
E) 2x-(3x-7)/4=x+1 |*4
8x-(3x-7)=4x+4
8x-3x+7-4x=4
x=4-7
x=-3

g) (x-1)/3-(x-2)/2=(2x-5)/6 |*6
2(x-1)-3(x-2)=2x-5
2x-2-3x+6-2x=-5
-3x=-5+2-6
-3x-9 |:(-3)
x=3

i) (x+6)/2-(5+x)/3=(2-x)/6 |*6
3(x+6)-2(5+x)=2-x
3x+18-10-2x+x=2
2x=2-18+10
2x=-6 |:2
x=-3

j) (2x-3)/6-(8-x)/9=(x+13)/18 |*18
3(2x-3)-2(8-x)=x+13
6x-9-16+2x-x=13
7x=13+9+16
7x=38 |:7
x=5i 3/7

k) (x+3)/3- (2+x)/4= (3-2x)/12 |*12
4(x+3)-3(2+x)=3-2x
4x+12-6-3x+2x=3
3x=3-12+6
3x=-3 |:3
x=-1

l) 2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2 |:(-2)
x=1

ł) 7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4
-3x-x+2x=1-4-7+4
-2x=-6 |:(-2)
x=3

m) 4-2(5-x) = x-4(x-1)
4-10+2x=x-4x+4
2x-x+4x=4+10-4
5x=10 |:5
x=2